QOLP-06. EXISTENTIAL DISTRESS: UNADDRESSED CONCERNS FOR ADULT NEURO-ONCOLOGY PATIENTS. (11th November 2019) - Loughan, Ashlee; Braun, Sarah; Husain, Mariya; Aslanzadeh, Farah; Boutte, Rachel; Lanoye, Autumn
Abstract: BACKGROUND: Primary brain tumor (PBT) patients may experience existential distress including fear of cancer recurrence and death anxiety; however, to date few have examined this issue. The objectives of this study were twofold: first, to systematically review PBT representation in the psycho-oncology literature on existential distress, and second, to preliminarily assess the prevalence and correlates of existential distress in a sample of PBT patients. PRIMARY OBJECTIVE METHODS/ RESULTS: Three databases (PsycINFO, PubMed, and CINAHL) were systematically searched to identify articles measuring fear of cancer recurrence, fear of dying, or death anxiety in oncology patients. Included studies were examined to determine the frequency of PBT patients and identify exclusion criteria relevant to neuro-oncology. For studies including PBT patients, a more thorough data extraction was undertaken. Systematic searching found 336 studies meeting inclusion criteria (N=133, 027). Eight studies (0.16% of the participants) included PBT patients. Exclusion criteria such as cognitive impairment and specific treatment parameters may have prohibited PBT patient participation. Studies including PBT patients used mixed methods with limited demographic analyses; existential distress was correlated with heightened psychological distress and poor quality of life. SECONDARY OBJECTIVE METHODS/ RESULTS: A cross-sectional analysis of 81 PBT patients (20–86 years old) was conducted. Patients completed validated questionnaires of death anxiety, death distress, generalized anxiety, and depressive symptoms. Descriptive analyses, t-tests, chi-square, and Pearson correlations were conducted. Up to 79% of PBT patients endorsed death anxiety. These patients were significantly younger, more likely to be female, and have a low-grade brain tumor (p< 0.05). Significant correlations were found between death anxiety and distress and symptoms of anxiety and depression (p< 0.01). CONCLUSIONS: PBT patients are underrepresented in existential psycho-oncology literature, despite preliminary findings suggesting prevalence of these concerns. Future investigations of existential distress in neuro-oncology is warranted to inform psychosocial screening and treatment for PBT patients.